A oposição à revolução constitucional portuguesa em 1820 - Um “folheto” censurado de F. J. da Madre de Deus (Ágora Journal, 2021)
In this contribution we look into an unpublished “pamphlet” by Justino José da Madre de Deus on the Portuguese Liberal Revolution, which was found in a Brazilian archive and that we publish in the Annex. The text was written at the end of September 1820, barely one month after the start of the Revolution in Oporto (the 24th of August). While the author is keen to defend consistently the establishment of constitutional monarchy and remains still very far away from the radical rejection of liberal constitutionalism that would become the major feature of his political writings from 1923 onwards, in this writing the deep differences with the revolutionary constitutional project were already evident, bringing about its prohibition by the liberal censorship committee established in Lisbon.